The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12887-020-1920-x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry, dietary intake, physical activity and sitting time patterns in adolescents aged 15–17 years: an international comparison in eight Latin American countries

Abstract: Background: Although there is high prevalence of obesity and other cardiovascular risk factors among Latin American adolescents, there is limited evidence on dietary intake and physical activity (PA) patterns in this population. Therefore, we characterized anthropometry, dietary intake, PA and sitting time (ST) in adolescents aged 15-17 years from eight Latin American countries.Methods: Six hundred seventy-one adolescents (41.4% girls) from the Latin American Study of Nutrition and Health (ELANS) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…We used only the questions that covered the active transport-related domain [21]. The IPAQ has been validated to assess PA in individuals aged 15-69 years in several countries [28,29].…”
Section: Walking and Cycling For Transportmentioning
confidence: 99%
“…We used only the questions that covered the active transport-related domain [21]. The IPAQ has been validated to assess PA in individuals aged 15-69 years in several countries [28,29].…”
Section: Walking and Cycling For Transportmentioning
confidence: 99%
“… 18 In addition, few studies have shown the pattern of total and domain-specific PA in adolescents living in megacities in low-income to middle-income countries. 19 …”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, few studies have shown the pattern of total and domain-specific PA in adolescents living in megacities in low-income to middleincome countries. 19 In the urban context of Sao Paulo, characterised by social fragmentation and inequalities in opportunities to engage in PA, the New Master Plan has emerged as an effective initiative to promote active life. 20 This initiative improved an extensive network of bike paths created in Sao Paulo in 2014.…”
mentioning
confidence: 99%
“…Physical activity (PA) was assessed using the self-administered version of the Spanish language long-form for the last seven days of the International Physical Activity Questionnaire (IPAQ) [ 32 ]. The IPAQ, which has been extensively used in Latin America [ 32 , 33 , 34 ], contains questions about the amount of walking, moderate and vigorous PA occurring as part of active transport and in leisure time. Only the sections about transport, sitting time and leisure-time PA were included in the ELANS [ 35 ].…”
Section: Methodsmentioning
confidence: 99%